The moderating impact of community-built environments on a behavior intervention program to increase health outcomes for insufficiently active adults - Natália Santos; Adalberto A.S. Lopes; Tânia Benedetti; Cassiano R. Rech (Clinical Epidemiology and Global Health, 2025)
Objective: The purpose of this study is to verify if the benefits obtained in behavioral variables by intervention participants of the “Active Life Improving Health” (VAMOS) program were associated with access to places for physical activity and healthy eating. Methods: Street network buffer areas of 500- and 1000-m were created around residences of VAMOS’ participants, healthy adults older than 18 years old (n = 125). Built environment's exposure variables were accounted for by the frequency of physical activity and healthy eating places in each buffer, and geo-referenced in Google Earth. Behavior variables focus on the primary health outcomes of VAMOS (i.e., sedentary behavior, moderate to vigorous physical activity, quality of life). Geospatial software was used to develop the walkability index in participants' census tracts. Results: There are significant interactions (p < 0.05) on how the presence of Leisure Public Spaces at 500-m decreased sedentary behaviors (p = 0.046) and waist circumference (p = 0.038) and increased physical activity levels (p = 0.001) in participants from baseline to the end of the program at 12 weeks. Walkability indices did not impact behavior change. Conclusions: Having Leisure Public Spaces and food retailers that sell healthy foods within 500-m of participants can influence positive behavior change. Walkability levels did not directly impact behavior change, which could be a result of how participants perceive walkability in their communities, and what their threshold is for considering spaces unfit or unsafe for walking. Future studies should consider locations post-COVID and assess the perception of participants on how they move around their communities.